2016
DOI: 10.1002/hec.3387
|View full text |Cite
|
Sign up to set email alerts
|

Doctor Competence and the Demand for Healthcare: Evidence from Rural China

Abstract: The agency problem between patients and doctors has long been emphasised in the health economics literature, but the empirical evidence on whether patients can evaluate and respond to better quality care remains mixed and inconclusive. Using household data linked to an assessment of village doctors' clinical competence in rural China, we show that there is no correlation between doctor competence and patients' healthcare utilisation, with confidence intervals reasonably tight around zero. Household perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…It is noteworthy that 33.9% were willing to accept DR after a doctor's advice. Due to the asymmetrical information between patients and doctors [46], patients rely more on the doctor's advice when making medical decisions. However, one study found that only 20.8% of doctors in tertiary hospitals are willing to recommend DR when the patient meets the criteria for referral [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that 33.9% were willing to accept DR after a doctor's advice. Due to the asymmetrical information between patients and doctors [46], patients rely more on the doctor's advice when making medical decisions. However, one study found that only 20.8% of doctors in tertiary hospitals are willing to recommend DR when the patient meets the criteria for referral [30].…”
Section: Discussionmentioning
confidence: 99%
“…tend to bypass primary care facilit ies and go directly to higher level hospitals even for minor conditions , which may lead to healthcare cost escalation (Fe et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous literature has found substantial gaps in the quality of healthcare between primary care facilit ies and hospitals, in terms of the management of chronic d iseases (Li et al, 2017), treat ment errors (Sylv ia et al, 2014) and overuse of antibiotics (Yin et al, 2013) and in jections (Liu et al, 2015a, Yang et al, 2014. In addition, most patients have an unrealistic expectation towards specialised hospital care, and their sceptics about the quality of primary care are not necessarily related with the true quality level (Fe et al 2016). Patients tend to…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For example, empirical studies have confirmed that patients’ perceptions of quality and observable signals (e.g., medicine and medical equipment availability) are related to patients’ healthcare-seeking behaviors [ 26 ]. However, the previous literature has shown no significant correlation between patients’ self-reported assessment of PHC quality and record-based quality [ 34 ] or clinicians’ medical knowledge [ 35 ]. Studies have also found no association between observable signals and healthcare quality [ 36 ].…”
Section: Introductionmentioning
confidence: 99%